Strategi Resiliensi dalam Menghadapi Beban Ekonomi Keluarga oleh Buruh Pabrik di Kota Banjarmasin - Bahjah, Noor; Hidayah, Sri (Prodi Sosiologi FISIP ULM, 2025)
Laborer families at the Super Sohun Factory in Banjarmasin City face severe economic challenges due to their low weekly income, which ranges only between Rp300,000 and Rp400,000. This amount is significantly below the city’s minimum wage and is insufficient to meet the rising cost of living. This study aims to identify the resilience strategies adopted by laborer families to fulfill their basic needs and examine how these strategies contribute to the continuity of essential family functions despite adversity. A qualitative research design was used with a phenomenological approach. The study was conducted in the South District, Banjarmasin City. Data were collected through field observation, in-depth interviews with key informants, and documentation. The data analysis used Miles and Huberman’s interactive model: data reduction, data display, and conclusion drawing. Findings indicate that the families build resilience through the effective use of five livelihood assets: social, human, financial, natural, and physical capital. They endure hardship by working hard, practicing frugality, leveraging social support, and embedding values of simplicity and cooperation. These strategies enable them to maintain crucial family roles such as child-rearing, education, and household harmony. Theoretically, this study contributes to the discourse on urban family sociology and resilience in impoverished settings. Practically, it offers insights for local government policy in designing social protection programs that genuinely support the resilience of urban working-class families.